2020
DOI: 10.1108/er-11-2019-0425
|View full text |Cite
|
Sign up to set email alerts
|

Employee stress and the implication of high-power distance culture: empirical evidence from Nigeria's employment terrain

Abstract: PurposeThis paper explores the link between employee stress and the high-power distance (HPD) culture in Nigeria. The study context is the banking and manufacturing sectors in Nigeria, which have a history of exploitation, unconducive work environments to productivity, work-life imbalance, work overload, burnout and employee stress.Design/methodology/approachUsing a qualitative, interpretive methodology, this article adopts a thematic analysis of data drawn from semi-structured interviews with 24 managerial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…However, there is a dearth of scholarship on how employee stress can be managed via management-leadership compassion in an extreme situation such as the current COVID-19 pandemic, which can cause extreme degrees of chaos and uncertainty as well as unprecedented demands in terms of both the existing workload and new procedures for managing health risks (WHO, 2020a, b). Focussing on Nigeria (the context), the study involves the banking, manufacturing and health sectors, which have a history of work-related stressors (exploitation, work environments unconducive to productivity, work overload), employee stress (Oruh and Dibia, 2020) and absence/inadequacy of effective management-leadership, which is crucial in responding to this stressful situation (Oshagbemi, 2017). In doing so, the study has (hopefully) made important empirical and theoretical contributions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a dearth of scholarship on how employee stress can be managed via management-leadership compassion in an extreme situation such as the current COVID-19 pandemic, which can cause extreme degrees of chaos and uncertainty as well as unprecedented demands in terms of both the existing workload and new procedures for managing health risks (WHO, 2020a, b). Focussing on Nigeria (the context), the study involves the banking, manufacturing and health sectors, which have a history of work-related stressors (exploitation, work environments unconducive to productivity, work overload), employee stress (Oruh and Dibia, 2020) and absence/inadequacy of effective management-leadership, which is crucial in responding to this stressful situation (Oshagbemi, 2017). In doing so, the study has (hopefully) made important empirical and theoretical contributions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yange et al (2016), the manufacturing sector has remained stagnate and underdeveloped due to weak infrastructure, political instability, unneeded bureaucracy and corruption. Oruh and Dibia (2020) noted that the sector largely employs unskilled, low-skilled and untrained workers because the operators are less interested in training (or investing in skilled) workers. Despite these limitations, Yange et al (2016) observed that employees are stretched beyond normal working hours in order to meet the unrealistic targets set by the management, which creates stress for the workforce.…”
Section: Study Context: Nigeria's Employment Terrainmentioning
confidence: 99%
See 1 more Smart Citation
“…Antecedents of work stress originating from work itself include workload (Harry, 2020;Oruh et al, 2020;Pandey, 2020;Sidhu et al, 2020), work environment (Oruh et al, 2020;Sidhu et al, 2020), work intensification (Walker, 2020), administrative/organizational pressure (Allison et al, 2019), work/job involvement (Li et al, 2018, Park andJang, 2017), work demands (Wijewardena et al, 2020), time pressure ( Amirudin, 2019), working conditions (Goswami et al, 2019), evaluation and performance appraisal systems (Pandey, 2020) and the uncertainty of working conditions (Hampton et al, 2019).…”
Section: Antecedents Of Work Stressmentioning
confidence: 99%
“…Relationships in the organization are a source of work stress. In the literature study conducted by the author, the antecedents of work stress are related to relationships in organizations including organizational structure (Naoum et al, 2018), leadership (Elomaa et al, 2020;Manoppo, 2020;Paeveen and Adeinant, 2019;Yao et al, 2020), social support (Bjaalid, 2020;Foy et al, 2018;Yousaf et al, 2020), communication and management support (Pandey, 2020;Sahni, 2020), culture high power distance (Hampton et al, 2019;Oruh et al, 2020), autonomy (Patel and Wolfe, 2019) and work team coordination (Hampton et al, 2019).…”
Section: Antecedents Of Work Stressmentioning
confidence: 99%